2019
DOI: 10.1103/physrevmaterials.3.084408
|View full text |Cite
|
Sign up to set email alerts
|

Orienting anisometric pores in ferroelectrics: Piezoelectric property engineering through local electric field distributions

Abstract: Ferroelectrics are a technologically important class of materials, used in actuators, sensors, transducers, and memory devices. Introducing porosity into these materials offers a method of tuning functional properties for certain applications, such as piezoand pyroelectric sensors and energy harvesters. However, the effect of porosity on the polarization switching behaviour of ferroelectrics, which is the fundamental physical process determining their functional properties, remains poorly understood. In part, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 70 publications
3
28
0
Order By: Relevance
“…45 In their next work, series-connected with respect to the freezing direction were prepared. They found that the remnant polarization decreased with an increase in orientation angle, 127 which was related to the local electric field distribution within the porous microstructure, which on average both broadens and reduces in magnitude with increasing pore orientation angle. From the previous studies, it can be concluded that porous ferroelectric ceramics with parallelconnected structure had the highest remnant polarization.…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…45 In their next work, series-connected with respect to the freezing direction were prepared. They found that the remnant polarization decreased with an increase in orientation angle, 127 which was related to the local electric field distribution within the porous microstructure, which on average both broadens and reduces in magnitude with increasing pore orientation angle. From the previous studies, it can be concluded that porous ferroelectric ceramics with parallelconnected structure had the highest remnant polarization.…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%
“…However, the blocking force would also be reduced compared to dense materials due to the lower stiffness of porous ferroelectrics, so they may be more suitable for low-force actuation applications. 127 For acoustic projector applications, Butler derived a projector-transducer figure of merit (FoMv)…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%
“…Ferroelectric ceramics are widely applicable in electronic devices and are indispensable in actuators, high-dielectric-constant capacitors, piezoelectric sensors, and ultrasonic transducers [1][2][3]. Microstructural and crystallographic parameters, such as crystal structure [4], degree of crystallographic texture [5,6], lattice distortion [7], and porosity [8] are commonly used to tailor their application-relevant electrical and electromechanical properties. Grain-size engineering is one of the most important tools and was previously used to tailor properties, such as permittivity [9], strain [10], fracture toughness [11], polarization reversal [12], electrical fatigue [13], high-power piezoelectric properties [14], and even phase transitions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the average d 33 of the PbZr 0.2 Ti 0.8 O 3 thin film obtained from the PFM amplitude loops (recorded at a frequency away from resonance), is ≈40 pm V −1 , indicating that the tip loading force could induce a piezoelectric field of 2.5 MV cm −1 . In principle, the piezoelectric field has an opposite direction to the original polarization direction, because the piezoelectric coefficient has opposite signs for different polarization states, [ 48 ] while the flexoelectric field always points from the surface of the film toward the substrate. When the high tip pressure is applied to the film with the downward polarization, the internal electric fields induced by the flexoelectric and the piezoelectric effects point to the opposite directions, however, the piezoelectric electric field is much stronger than the flexoelectric field and the negative coercive field.…”
Section: Resultsmentioning
confidence: 99%
“…The observed upward switching of domains can be attributed to the combined effects of the built-in electric field and the mechanical force. [41][42][43]47] It was reported that both piezoelectric effect and flexoelectric effect can be induced by the strain and the strain gradient imposed by the tip, [48][49][50][51][52] and they could induce an internal electric field in the film. When a loading force of 3051.8 nN is applied to the film by a PFM tip with a radius of 25 nm, it will induce a high pressure of ≈1.5 GPa.…”
Section: Figures 2amentioning
confidence: 99%